ANALISIS ANTENATAL CARE (ANC) PADA SURVEILANS KESEHATAN IBU DAN ANAK DENGAN TAHAPAN AGREGASI PIPELINE NOSQL - Dadang Heksaputra; M. J. U. Haris Bahrudin; Anni Karimatul Fauziyah; Dhina Puspasari Wijaya (Program Studi S1 Sistem Informasi Fakultas Komputer dan Teknik Universitas Alma Ata, 2021)
Case 30.8 percent of Indonesian children under five are stunted. Bantul is a district in the Province of D.I. Yogyakarta, Indonesia, is a locus of stunting. Bantul has ten villages. The ten villages include Patalan Jetis Village, Canden Jetis Village, Terong Dlingo Village, Argodadi Sedayu Village, Triharjo Pandak Village, Triwidadi Pajangan Village, Jatimulyo Dlingo Village, Datangharjo Sewon Village, Sendangsari Pajangan Village, and Trimulyo Jetis Village. The research focuses on the village of Argodadi Sedayu. In the village of Argodadi Sedayu, Antenatal Care (ANC) research would be conducted. Antenatal Care (ANC) is a pregnancy check by a doctor or midwife. Therefore, Antenatal Care Analysis (ANC) is needed to determine whether diet, parenting, and sanitation are well programmed. Antenatal care (ANC) research framework was a model of method improvement. The method improvement model consists of indicators, proposed methods, objectives, and measurements. The indicators consist of monitoring instruments and health visits. The proposed method uses an aggregation pipeline stage. The data was processed in the aggregation pipeline stage. The data were obtained from the time series data surveillance dataset. The research objective was to analyze the research results accurately according to the proposed method. Measurement of indicator analysis with the application of the dashboard as a performance indicator on the research results. Practically, it is hoped that the research results could consider the health office and related institutions in reducing or even elevating Argodadi Sedayu Village in Yogyakarta as a non-locus of stunting using massive monitoring of diet, parenting, and sanitation well programmed.